Asthma and coagulation - de Boer, J Daan; Majoor, Christof J; van 't Veer, Cornelis; Bel, Elisabeth H D; van der Poll, Tom (Blood, 2012)
Asthma is a chronic airway disease characterized by paroxysmal airflow obstruction evoked by irritative stimuli on a background of allergic lung inflammation. Currently, there is no cure for asthma, only symptomatic treatment. In recent years, our understanding of the involvement of coagulation and anticoagulant pathways, the fibrinolytic system, and platelets in the pathophysiology of asthma has increased considerably. Asthma is associated with a procoagulant state in the bronchoalveolar space, further aggravated by impaired local activities of the anticoagulant protein C system and fibrinolysis. Protease-activated receptors have been implicated as the molecular link between coagulation and allergic inflammation in asthma. This review summarizes current knowledge of the impact of the disturbed hemostatic balance in the lungs on asthma severity and manifestations and identifies new possible targets for asthma treatment.